Instrumenty marketingowe wykorzystywane w konkurencji usług gastronomicznych (na przykładzie powiatu mieleckiego) - Grzybek, Maria; Szopiński, Wiesław (Marketing Instruments Used in Rivalry Between Catering Services (on the Example of Mielec Poviat), 2006)
The competitiveness is one of fundamental and permanent phenomena characterizing market economy. It is an essential element of economic life. Its occurence motivates rivals to act efficiently and use the limited resources effectively. It also motivates to progress, to increase quality of goods and services for the benefit of consumers. The entrepreneurs acting on the market of catering services in Mielec Poviat use basic instruments of rivalry but with various intensity. In particular they have paid attention to elements connected with price and high quality of offered products. The other elements of marketing activities are used to a smaller degree, especially in the range of distribution, brand and the uniqueness of an offer.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 282-287